CD69 is a direct HIF-1α target gene in hypoxia as a mechanism enhancing expression on tumor-infiltrating T lymphocytes - Sara Labiano (OncoImmunology, 2017)
CD69 is an early activation marker on the surface of T lymphocytes undergoing activation by cognate antigen. We observed intense expression of CD69 on tumor-infiltrating T-lymphocytes that reside in the hypoxic tumor microenvironment and hypothesized that CD69 could be, at least partially, under the control of the transcriptional hypoxia response. In line with this, human and mouse CD3-stimulated lymphocytes cultured under hypoxia (1% O2) showed increased expression of CD69 at the protein and mRNA level. Consistent with these findings, mouse T lymphocytes that had recently undergone hypoxia in vivo, as denoted by pimonidazole staining, were more frequently CD69+ in the tumor and bone marrow hypoxic tissue compartments. We found evidence for HIF-1α involvement both when using T-lymphocytes from inducible HIF-1α−/− mice and when observing tumor-infiltrating T-lymphocytes in mice whose T cells are HIF-1α−/−. Direct pro-transcriptional activity of HIF-1α on a newly identified hypoxia response element (HRE) found in the human CD69 locus was demonstrated by ChIP experiments. These results uncover a connection between the HIF-1α oxygen-sensing pathway and CD69 immunobiology.